Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Kantor Kecamatan Ciputat - Apriliana, Rina; Prasetyo, Hendri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 43 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study of motivation and work discipline on employee performance". Shown by the multiple linear regression equation Y = 14,962 + 0,460 + 0,162. This is evidenced by the results of the simultaneous hypothesis test obtained the value of f count> f table (11,675> 3,23) and strengthened by the significance value <0.05 (0.000 <0.05). The results of the determination coefficient test of the motivation and work discipline variables have an influence of 36,9%.on employee performance. Thus, H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between motivation (X1) and work discipline (X2) on employee performance (Y).